New records of small mammals in the diet of the buff-fronted owl, Aegolius harrisii and the black-and-white owl, Strix nigrolineata, along with a review of mammal prey of owls in Colombia - Marín-Giraldo, Valentina; Chaves-Castaño, Sarah; Mejía-Fontecha, Ingrith Y.; Velásquez-Guarín, Daniela; Mejía-Egas, Ofelia; López-Ordoñez, Juan Pablo; Ramírez-Chaves, Héctor E. (Therya Notes, 2023)
The diet of Colombian owls has been scarcely studied. The consumption of bats and other small mammals has been recorded for Aegolius harrisii and Strix nigrolineata in Central and South America; however, there was no information on this topic in Colombia for both species. We present new observations of the predation of mammals by owls in Colombia and a brief review of historical records. We reported the attempt of consumption of a bat of genus Platyrrhinus by the buff-fronted owl (Aegolius harrisii) and the presence of bats (Dermanura and Rhogeessa) and shrews (Cryptotis) in one pellet of the black-and-white owl, Strix nigrolineata, in the Andes of Colombia. The literature review showed that at least 30 mammal species have been recorded in the diet of 8 additional owl species in the country. Rodents are the prey with the highest number of reports, which include taxa from forested, urban, and peri-urban areas. This information might be useful for subsequent studies on the possible effects of habitat loss on mammal consumption by owls and the role as a controller of zoonotic agent hosts.